Analisis dan Perancangan Sistem Enterprise Resource Planning Berbasis Web untuk Optimalisasi Manajemen Retail pada UMKM - Wahyu Sugiarto; Farizi Ilham (PT. Saha Kreasi Indonesia, 2026)
This research discusses the analysis and design of a web-based Enterprise Resource Planning (ERP) system to optimize retail management for Micro, Small, and Medium Enterprises (MSMEs). The background of this research is the low adoption of digital technology among retail MSMEs in Indonesia, which causes stock management inefficiencies, slow transaction processes, and unstructured financial reports. The development method uses the prototyping approach with iterative cycles. The system was built with React.js frontend, Laravel backend, and MySQL database, implementing 12 main modules. Testing results show all modules function according to specifications with 100% stock accuracy, transaction speed increased 3 times, and real-time financial reports.